2020
DOI: 10.1016/j.waojou.2020.100099
|View full text |Cite
|
Sign up to set email alerts
|

Novel salivary gland allergens from tropical mosquito species and IgE reactivity in allergic patients

Abstract: Background: Mosquito allergy is common in tropical countries but remains under-diagnosed.This may be due to the lack of knowledge and diagnostic tools for tropical mosquito allergens.Objective: We aimed to characterize allergens from tropical mosquito species and investigate IgE reactivity in mosquito-allergic patients to the salivary gland proteins from these mosquitoes.Methods: Salivary gland extract (SGE) from 4 mosquito species, highly distributed in the tropics, including Aedes aegypti, Aedes albopictus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Aed a 4 is a 67 kDa α-glucosidase. About 36-46% of mosquito allergic individuals react against this allergen (19,54).…”
Section: Group 3 and 4 Mosquito Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…Aed a 4 is a 67 kDa α-glucosidase. About 36-46% of mosquito allergic individuals react against this allergen (19,54).…”
Section: Group 3 and 4 Mosquito Allergensmentioning
confidence: 99%
“…This finding is similar in other tropical countries where high occurrence of mosquitoes and HDMs results in high prevalence of allergic sensitization ( 18 ). The observations open questions about the magnitude of the clinical impact produced by sensitization to mosquitoes and postulate the need for developing diagnostic tests to properly identify individuals with mosquito allergy ( 19 ). In this context, the comparison of mosquito prevalence and the frequency of sensitization to their allergens in tropical and other regions around the world should be further addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The immunogenicity of Culex spp. saliva has been a topic of interest, but most studies focused on identifying the main immunogenic salivary proteins responsible for allergy so as to develop high-sensitivity diagnostic tests and immunotherapy [ 29 , 30 ]. Studies identified Cx .…”
Section: Introductionmentioning
confidence: 99%
“…Studies identified Cx . quinquefasciatus salivary proteins that elicit an IgE and IgG responses in humans, with the major antigens being the D7-related proteins[ 30 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation